Transmission electron microscopy of the scolex and neck microtriches of Silurotaenia siluri (Batsch, 1786) (Cestoda: Proteocephalidea) - Zdárská, Z; Nebesárová, J (Parasitology research, 2005)
Microtriches on different parts of the scolex and neck of the gangesiine cestode Silurotaenia siluri (Batsch 1786) were studied. The neodermis of the central frontal scolex part (around the rostellar furrow) bears filamentous microtriches only. The lateral frontal part and the parts between and posterior to the suckers cover filamentous and spine-like microtriches. Within the suckers there are short spine-like microtriches with bases enforced by electron-dense ribs. The proximal neck part bears filamentous and spine-like microtriches, the middle part solitary distributed blade-like and spine-like microtriches among filamentous ones, and the distal part blade-like microtriches. The functions of different types of microtriches are discussed.
Keywords: sumci; střeva; transmisní elektronová mikroskopie; Cestoda; Animals; Catfishes; Intestines; Fish Diseases; Microscopy, Electron, Transmission; zvířata; nemoci ryb